Platelet-Rich Plasma in Female Androgenic Alopecia: A Comprehensive Systematic Review and Meta-Analysis - Zhou, Shuying; Qi, Fei; Gong, Yue; Zhang, Chenxi; Zhao, Siqi; Yang, Xutong; He, Yanling (Frontiers in Pharmacology, 2021)
Introduction: The population of young women who suffered from female pattern hair loss (FPHL) or female androgenic alopecia (AGA) is gradually increasing. Platelet-rich plasma is a novel and promising therapeutic method as a nonsurgical treatment for FPHL. Objective: To summarize different preparation methods of PRP and treatment regimes in FPHL, qualitatively evaluate the current observations, and quantitively analyze the efficacy of PRP in FPHL treatment. Methods: Six databases, MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, LILACS, and CNKI, were searched with terms “platelet-rich plasma,” synonyms for AGA and FPHL. Meta-analysis was conducted with enrolled observational studies and randomized controlled trials separately. Results: We evaluated 636 studies and 12 trials from all searched databases. A total of 42 studies of 1,569 cases, including 776 female participants covering 16 randomized controlled trials and 26 observational trials, were included for qualitative synthesis study and systematic review. PRP showed positive efficacy in treating FPHL in hair density compared to the control groups with odds ratio (OR) 1.61, 95% CI 0.52–2.70, and compared to baseline with OR 1.11, 95% CI 0.86–1.37. Conclusion: PRP showed excellent efficiency as a novel therapy of FPHL through hair density evaluation. Further studies are needed to define standardized protocols, and large-scale randomized trials still need to be conducted to confirm its efficacy.